Pro Expression Blend 4 - Troelsen, Andrew W. (Expert's voice in Expression Blend., 2011)
Focuses on Blend IDE and its potential for application developers, including a through overview of Blend basics and a second section for readers who want to go more in depth with information on such topics as vector graphics, animation, GUI controls, data binding, and prototyping.